2003
DOI: 10.1074/jbc.m302979200
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Endoplasmic Reticulum-associated Pathways Degrade Mutant Yeast Carboxypeptidase Y in Mammalian Cells

Abstract: The degradation of misfolded and unassembled proteins by the endoplasmic reticulum (ER)-associated degradation (ERAD) has been shown to occur mainly through the ubiquitin-proteasome pathway after transport of the protein to the cytosol. Recent work has revealed a role for N-linked glycans in targeting aberrant glycoproteins to ERAD. To further characterize the molecular basis of substrate recognition and sorting during ERAD in mammalian cells, we expressed a mutant yeast carboxypeptidase Y (CPY*) in CHO cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 63 publications
1
30
1
Order By: Relevance
“…The fusion gene was then inserted downstream of the Aspergillus nidulans gpdA promoter in a plasmid containing a hygromycin resistance cassette, using the XbaI sites incorporated into each primer. The coding sequence of the Af-CPY gene was then modified by site-directed mutagenesis using primers 657 and 658 to create Af-CPY* (G264R), which creates the same point mutation that targets CPY* for degradation in S. cerevisiae (G255R) (23). The plasmid was linearized with KpnI and SacI and introduced into wt and ⌬hrdA protoplasts as an ectopically integrated expression construct using standard transformation procedures, as previously described (6).…”
Section: Methodsmentioning
confidence: 99%
“…The fusion gene was then inserted downstream of the Aspergillus nidulans gpdA promoter in a plasmid containing a hygromycin resistance cassette, using the XbaI sites incorporated into each primer. The coding sequence of the Af-CPY gene was then modified by site-directed mutagenesis using primers 657 and 658 to create Af-CPY* (G264R), which creates the same point mutation that targets CPY* for degradation in S. cerevisiae (G255R) (23). The plasmid was linearized with KpnI and SacI and introduced into wt and ⌬hrdA protoplasts as an ectopically integrated expression construct using standard transformation procedures, as previously described (6).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, recently multiple mechanisms have been reported to target different substrate proteins through distinct degradative pathways (4,27,44,50). Among the alternative degradation pathways, some are described as independent of calnexin but involving the ER chaperone calreticulin (4) or BiP (44).…”
mentioning
confidence: 99%
“…Among the alternative degradation pathways, some are described as independent of calnexin but involving the ER chaperone calreticulin (4) or BiP (44). Another alternative pathway was found to be independent of cytosolic components but sensitive to either tyrosine phosphatase blockage or ER mannosidase I inhibition (27). Examples of substrates following such alternative pathways are mutant variants of ␣1-antitrypsin (4), carboxypeptidase Y (27), and tyrosinase (44,50).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While Ub-mediated degradation is the most common pathway for ERAD (9,31,49), LPL degradation was unaffected by proteasomal inhibitors (23). Indeed, other examples indicate that multiple, nonproteasomal pathways of ERAD exist (50,51). However, in this study, we identified several proteins that suggest HL degradation is Ub mediated: CNX, Grp78, Grp94, and eEF1A are all established players in Ub-mediated degradation (9,31,33,49).…”
Section: Hl Degradation Occurs Via the Proteasomal Pathwaymentioning
confidence: 61%